Evaluation Interleukin â”€ 8 and High Sensitivity C - Reactive Protein in Sera of Control Group and Human Female Patients with Osteoarthritis Nodal in Iraqi's Patients - AL-Wihaly, B. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study conducted on 30 female patients with osteoarthritis OA a attending Baghdad teaching hospital, in addition to 30 healthy females, all subjects were (35-65) year's old .Parameters were measured in the sera of patients group and healthy groups were interleukin -8 (IL-8) and high sensitivity C-reactive protein (hs-CRP).The results revealed a higher significant in all parameters of patients sera compared to healthy groups. Conclusion was obtained that IL-8 and hs- CRP were a markers or player inflammatory disease like osteoarthritis nodal